Dampak Upah Minimum Regional dan Pertumbuhan Penduduk Terhadap Penyerapan Tenaga Kerja pada Industri Kecil Menenggah di Kabupaten Nagan Raya - Alisman Alisman; Uswatun Hasanah; Zulfan Yusuf; Nurfiani Syamsuddin; Dedi Sufriadi (eCo-Buss, 2022)
The final project entitled the impact of Regional Minimum Wages and Population Growth on Labor Absorptionin Small and Medium Industries in Nagan Raya Regency aims to determine how much the relationship and influence of the amount of the Regional Minimum Wages and population growth on Labor Absorptionin Nagan Raya Regency, the data collection techniques used is literature study and field research. This research data is secondary data in the form of time series (time series) for the period 2008 – 2019, obtained from the central statistics of Nagan Raya Regency and the Departement of Industry, Trde, Cooperativesl Small and Medium Enterprises. The data analysis model used is multiple linear regression analysis with the Ordinary Least Square (OLS). The results of hypothesis testing show that the t-value of tcount 4.694 > 1.833 t table whit a probability level of 0.001 which states that there is a positive and real influence of the Regional Minimum wage variable on laborabsorptionin small and medium industries in Nagan Raya Regency, and proves partially that the value of the population growth variable is -0.7066 < 1.833 t table with a probability level of 0.498 states that population growth has no effect on labor absorption in small and medium industriesin Nagan Raya Regency. The simultaneous hypothesis testing results prove that the regional minimum wage variables has a positive and significant effect on labor absorption in small and medium in Nagan Raya Regency with a probability level of 0.001< 0.05 with a correlation level of R= 0.7297 which means that there is a strong relationship between regional minimum wage and job absorption in small and medium industriesin Nagan Raya Regency.